Semantic Analysis of the Conceptual Structure of “Disease” in the Qur’anic Context - Ziyad Ravaşdeh; Hidayet Aydar; Khadeejeh Alrawashdeh; Mehmet Yalçın Yılmaz (UIN Sunan Kalijaga Yogyakarta, 2026)
This study examines the conceptual structure of “disease (maraḍ) within the Qur’anic lexicon, aiming to elucidate the epistemic network of Qur’anic maqāṣid dedicated to preserving human life and its environment. The central research problem lies in how the Qur’an articulates its vision of pathogenic afflictions that obstruct the realization of core human existential objectives, particularly the preservation of life- the foundational maqṣad in Islamic thought. As temporal and spatial conditions change, certain complementary (taḥsīniyyah) objectives may ascend to the rank of necessities (ḍarūriyyāt). The study’s significance rests in demonstrating the adaptability of Qur’anic maqāṣid across time and place, and their role in securing dignified human existence through safeguarding indispensable objectives: religion, intellect, lineage, property, and life itself. It also highlights the aesthetic-ethical philosophy embedded in relevant verses concerning societal privacy and personal dignity. Methodologically, the study adopts an inductive approach to pertinent Qur’anic verses, lexical-semantic analysis, and a historical survey of maqāṣid-oriented exegesis. This framework illuminates how the sacred text addresses pathogenic threats, ensures civilizational continuity, and manifests a distinctive lexical paradigm compared to post-Qur’anic Arabic lexicons. Key findings reveal that the Qur’an systematically links disease and cure to their causes while emphatically advocating preventive measures to curb epidemics, thereby reaffirming the enduring capacity of the Islamic normative framework to address contemporary challenges without compromising its ethical constants.